Management of Rice Blast (Magnaporthe Oryzae B. Couch) Using Bioagents and Fungicides Under Hill Rice Ecosystem of Uttarakhand State in India (Bangladesh Journal of Botany, 2021)
A field study was conducted during Kharif-2015 and 2016 on management of leaf and neck blast disease of rice caused by Magnaporthe oryzae under hill rice ecosystem. Different treatments including biological control agents like Trichoderma sp. and Pseudomonas sp. and chemical fungicides like tricyclozole, azoxystrobin and carbendazim were used at different growth stages of rice. Among the treatments, tricyclozole @ 0.06% was highly effective followed by azoxystrobin @ 0.1% with application immediately after appearance of disease. Trichoderma and Pseudomonas were not effective in reducing the disease pressure.Bangladesh J. Bot. 50(3): 713-716, 2021 (September)